The Magnetic Field in Quiescent Star-forming Filament G16.96+0.27 - Qi-Lao Gu; Tie Liu; Zhi-Qiang Shen; Sihan Jiao; Julien Montillaud; Mika Juvela; Xing Lu; Chang Won Lee; Junhao Liu; Pak Shing Li; Xunchuan Liu; Doug Johnstone; et al. (The Astrophysical Journal)
We present 850 μ m thermal dust polarization observations with a resolution of 14.″4 (∼0.13 pc) toward an infrared dark cloud G16.96+0.27 using James Clerk Maxwell Telescope/POL-2. The average magnetic field orientation, which roughly agrees with the larger-scale magnetic field orientation traced by the Planck 353 GHz data, is approximately perpendicular to the filament structure. The estimated plane-of-sky magnetic field strength is ∼96 μ G and ∼60 μ G using two variants of the Davis–Chandrasekhar–Fermi methods. We calculate the virial and magnetic critical parameters to evaluate the relative importance of gravity, the magnetic field, and turbulence. The magnetic field and turbulence are both weaker than gravity, but magnetic fields and turbulence together are equal to gravity, suggesting that G16.96+0.27 is in a quasi-equilibrium state. The alignment between the magnetic field and cloud is found to have a trend moving away from perpendicularity in the dense regions, which may serve as a tracer of potential fragmentation in such quiescent filaments.